2009
DOI: 10.7146/mediekultur.v25i47.1403
|View full text |Cite
|
Sign up to set email alerts
|

Actors and Their Use of Avatars as Personal Mediators: An empirical study of avatar-based sense-makings and communication practices in the virtual worlds of EverQuest and Second Life

Abstract: Over the past five years, millions of actors have found it meaningful to move in and settle down in the Metaverse, for example, as an adventurous shaman in an advanced role-playing game such as EverQuest or as a businesswoman in the social world of Second Life. In this article, the main question therefore is: how do the actors and gamers of the two types of virtual worlds make sense of their avatars and the worlds when they act and communicate using their avatars as personal mediators? Participatory observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Second Life gave rise to three newspapers focused on the events of the virtual world: the Alpaville Herald, the Metaverse Messenger, and the Second Life Newspaper (Brennen and Dela Cerna, 2010). In addition to these virtual-world newspapers, Second Life facilitated the Metanomics (Metaverse and economics) weekly interview program hosted by Robert Bloomfield (Jensen, 2009). Metanomics became so successful that Cruz and Fernandes (2011) described it as "the seminal form of what journalism will look like in the 21st century.…”
Section: Journalism In Second Lifementioning
confidence: 99%
“…Second Life gave rise to three newspapers focused on the events of the virtual world: the Alpaville Herald, the Metaverse Messenger, and the Second Life Newspaper (Brennen and Dela Cerna, 2010). In addition to these virtual-world newspapers, Second Life facilitated the Metanomics (Metaverse and economics) weekly interview program hosted by Robert Bloomfield (Jensen, 2009). Metanomics became so successful that Cruz and Fernandes (2011) described it as "the seminal form of what journalism will look like in the 21st century.…”
Section: Journalism In Second Lifementioning
confidence: 99%
“…Riva et al [28] have showed that virtual environments function as an affective media. Their affective nature has been explained by several factors including the sense of presence [28] and the playful and game-like characteristics of the environments [29,30]. Emotional intelligence is put into play especially when an activity demands high levels of personal commitment and interpersonal trust.…”
Section: Introductionmentioning
confidence: 99%